Digoxin absorption decreased independently of P-gp activity in rats with irinotecan-induced gastrointestinal damage - Toshiaki Tsuchitani; Takeshi Akiyoshi; Ayuko Imaoka; Hisakazu Ohtani (BMC, 2021)
Abstract Background Irinotecan (CPT-11) is clinically known to cause severe diarrhea and gastrointestinal damage. Recently, we have reported that CPT-11-induced gastrointestinal damage is associated with the upregulation of intestinal P-glycoprotein (P-gp) expression and decreased absorption of its substrate, dabigatran etexilate (DABE), using a rat model. However, the P-gp activity or its contribution to the decreased absorption remains unclear. The aim of this study was to quantitatively evaluate how P-gp activity changes in rats with CPT-11-induced gastrointestinal damage, as assessed by the absorption of digoxin (DGX), a typical P-gp substrate. Methods Male Sprague-Dawley rats were intravenously administered CPT-11 at a dose of 60 mg/kg/day for 4 days to induce gastrointestinal damage. Then, the rats were administered DGX orally (40 μg/kg), after some of them were orally administered clarithromycin (CAM; 10 mg/kg), a P-gp inhibitor. DGX (30 μg/kg) was administered intravenously to determine the bioavailability (BA). The rats' DGX plasma concentration profiles were determined using LC-MS/MS. Results CPT-11 treatment decreased the maximum concentration (Cmax) and area under the plasma concentration-time curve (AUCpo) of DGX, which does not contradict to the DABE study. Although in the CPT-11-treated group the BA of DGX was significantly decreased to 40% of the control value, CAM did not affect the BA of DGX in the CPT-11-treated group. Conclusions Increased P-gp expression in rats with CPT-11-induced gastrointestinal damage is not necessarily associated with increased P-gp activity or contribution to the drug absorption in vivo. The decreased DGX absorption observed in this study might be attributable to other factors, such as a reduction in the absorptive surface area of the gastrointestinal tract.